JEJAK METODOLOGIS ANTI-SUFI; ANALISIS KRITIS PEMIKIRAN SUFISME IBNU TAYMIYAH - Abdul Munim Kholil (Institut Dirosat Islamiyah Al-Amien Prenduan, 2017)
Sufism is an intergral part of Islamic belief and practicejust as the other religions have the mysticism. Sufism preference is human nature, sodenying it means ignoring human nature. It is natural as human being is a combination of undivided spirit and body.The presence of sufism among Muslims is not a peculiar issue. It is a part of Islam itself. However, that some Islamic scholars, which is natural, heavily criticized abused practice of Sufism makes sufis restless and disquiet. Critics are indeed necessary for inspiration and evaluation, but that the critics remove the Sufism from Islam is really unfair. The critics perceive sufism as an infiltrated entity into Islam and the disciples as heretics.This paper is aimed to critically analyze Ibn Taymiyah's thought of Sufism by examining the literature related to the track record of Ibn Taymiyah's thought about with Sufism and the methodology it offers. The result shows that there are three main points of Ibn Taymiyah commentary. Those aretariqah (devotional orders) institution, the knowledge resources and the doctrine of duality of inward-outward and sharia-haqiqah. Ibn Taymiyah commented on these using the analysis method of hadith experts (literalist-scripts) by self-sufficient reading the Sufis works and conducting structuralist studies of the Sufi texts.